25p-12=

Simple and best practice solution for 25p-12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25p-12= equation:


Simplifying
25p + -12 = 0

Reorder the terms:
-12 + 25p = 0

Solving
-12 + 25p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 25p = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 25p = 0 + 12
25p = 0 + 12

Combine like terms: 0 + 12 = 12
25p = 12

Divide each side by '25'.
p = 0.48

Simplifying
p = 0.48

See similar equations:

| 5(p)+2(1-p)=4(p)+7(1-p) | | -3(y+9)=36 | | -9a^6c^4(5c^3+3a-6)= | | v/9=11/5 | | 2b^2-13b+6=0 | | -4y-y-6=14 | | -7x-2=-30 | | 7/3=9/u | | 0.20x+0.45(50)=33.5 | | A(r)=4(3.14)r^2 | | 4p+3(1-p)=p+7(1-p) | | 25=9+(9x+2) | | -d+46=26 | | 1x+9= | | x^2+4x+y^2+6y+63=0 | | -4+46=26 | | 110=-10-8x | | 9x+4y=65 | | 2(4k-3)=3k-38 | | m/5 | | 6b-3=5a+1 | | -4p+(-1)(1-p)=1p+(-2)(1-p) | | 118/13=u/6 | | 3/5=y/7 | | 45x+32m=6 | | 2a+6=3a-10 | | 4w-21+7w=45 | | (7y+6)-(4+6y)=8 | | -6y+12+2y=40 | | Xsquared+10x+6=0 | | -5x=1+x-4-3x | | (3c-4t)(3c+3t)= |

Equations solver categories